Financing urban development by taxes: European experience - Yana Kalustyan (Cхід, 2014)
At this stage of its formation, Ukraine is on its way to European integration. This process involves not only the scope of the political life of the state but also economic policy. By ratifying the Charter of Local Self-Government, Ukraine has confirmed that it shall comply with its provisions. Article 9 of the Charter provides that at least a portion of the financial resources of local self-government should be formed at the expense of own revenues of municipalities. Such income includes tax revenues. At this stage of the budgetary system of Ukraine's total share of income of local taxes and fees in local budgets is insufficient to fund the operation of local government. Well-known is the fact that the effectiveness of local government largely depends on how much of their own resources available at its disposal. While the hallmark of developed European countries is to strengthen the role of local budgets, the main component of which in many countries are local taxes. At the present stage of development of the budget and tax system of Ukraine will be useful to study the experience of developed countries in Europe with regard to the financing of socio- economic development of cities by tax revenues.